The Risk Mitigation of Mitraguna Financing to Collectability 5 Customers at Bank Syariah Indonesia - Mohammad Syaiful Suib; Bagas Deo Pradana (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
The purpose of this research is to understand the methods and strategies employed by Bank Syariah Indonesia to mitigate and minimize banking risks, particularly financing risks, in its business operations. This study utilizes a literature review methodology, collecting references from previous research and examining various journals to review the banking risk mitigation strategies. Bank Syariah Indonesia is a financial institution and a subsidiary of a state-owned enterprise (BUMN) that operates based on Sharia principles. In the course of its business activities, the bank faces potential risks. Therefore, Bank Syariah Indonesia must be able to mitigate the occurrence of risks, especially in financing products. To mitigate risks, Bank Syariah Indonesia implements strategies such as evaluating prospective customers using the 7 P approach and assessing their financial capabilities through the Debt Service Ratio (DSR) and Debt Burden Ratio (DBR).